Analisis Rasio Likuiditas, Solvabilatas, Aktivitas Dan Profitabilitas Dalam Mengukur Kinerja Keuangan Pada Pt Adhi Karya Tbk Sebelum Dan Sesudah Covid-19 - Muh Khaerul Wildan; Sri Hermuningsih (Jurnal Mirai Management, 2022)
Abstract This study aims to determine, assess and analyze the financial performance of PT Adhi Karya Tbk by measuring using the liquidity ratio (current ratio), solvency ratio (debt to equity ratio), activity ratio (total assets turnover), and profitability (net profit margin). This research uses a quantitative descriptive method, the technique of collecting financial statement data from 2018 to 2021. Based on results analysis and discussion, performance finance with use current ratio year 2018 as large as 1,34, In 2019 there was a decrease to 1.23, in 2020 it decreased to 1.11, in 2021 there was a slight decrease of 1%, in general the average condition was below the industry standard. solvency ratio which measure with debt to equity ratio year 2018 down 72%, year 2019-2020 increase 85%, and year 2021 stable. Aktivity ratio which measure total asset turnover, year 2018 increase 52%, year 2019-2020 tends to decrease, year 2021 stable, this is due to a slight increase in sales. Profitability ratio which measue margin profit clean year 2018 experience drop 43%, year 2019 stable, year 2020 increase 68%, year 2021 little increase. Keywords: Liquidity Ratio, Solvancy Ratio, Aktivity Ratio, Profitability Ratio